New Insights Into the Anatomy of the Eyelashes With Regard to Ethnic Differences Against a Clinical Background. - Singh, Swati; Hammer, Christian; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2024)
BACKGROUND: To investigate the root depth, root angle, and light and scanning electron microscopical anatomy of human eyelashes relevant to eyelash ablation. METHODS: Eyelash root depth, the angle between eyelash root and skin epithelium, spatial relationship, and scanning electron microscopical features of the eyelashes were studied on 4 upper and 4 lower eyelids of Caucasian (n = 4) and Indian (n = 4) cadaver heads according to a set protocol. RESULTS: There were significant differences in the mean eyelash root depth between Indians (2.3 ± 0.38 mm) and Caucasians (1.9 ± 0.26 mm; p = 0.007), as well as between upper eyelids and lower eyelids (1.9 ± 0.2 mm vs. 1.8 ± 0.1 mm). The mean angle between the lash follicle root and the skin epithelium was 75 ± 11 degrees and similar in both ethnic groups. The eyelash bulb was located close to the tarsal plate and meibomian glands and formed an angle of less than 15 degrees with the eyelash root. Scanning electron microscopy studies revealed that the eyelash bulb was 202 ± 12 μm wide in Indians and 170.6 ± 16.8 μm wide in Caucasian eyelids ( p = 0.08). The eyelashes were placed more closely in Indian eyelids than in Caucasian eyelids ( p = 0.03). The width of the cuticle layer varied between the hair shaft and the inner eyelid segment. CONCLUSIONS: There are differences in eyelash root depth, inter-eyelash distance, and cuticle thickness between Indian and Caucasian eyelids. The oblique orientation of the eyelash root and close proximity of the eyelash bulb to the tarsal plate should be kept in mind while doing the electroepilation procedure.
EVALuna2:545156